Intraoperative and early postoperative complications in postchemotherapy retroperitoneal lymphadenectomy among patients with germ cell tumors using validated grading classifications. Issue 22 (17th September 2020) - Umbreit, Eric C.; McIntosh, Andrew G.; Suk‐ouichai, Chalairat; Segarra, Luis A.; Holland, Levi C.; Fellman, Bryan M.; Williams, Stephen B.; Thomas, Arun Z.; Tu, Shi‐Ming; Pettaway, Curtis A.; Pisters, Louis L.; Ward, John F.; et al.
Abstract : Background: Postchemotherapy retroperitoneal lymphadenectomy (PC‐RPLND) is an essential, yet potentially morbid, therapy for the management of patients with advanced germ cell tumors. In the current study, the authors sought to define the complication profile of PC‐RPLND using validated grading systems for intraoperative adverse events (iAEs) and early postoperative complications. Methods: Between 2000 and 2018, all patients who underwent PC‐RPLND were analyzed for iAEs and early postoperative complications using the Kaafarani and Clavien‐Dindo classifications, respectively. Logistic regression models were conducted to assess patient and tumor factors associated with iAEs and postoperative complications. Results: Of the 453 patients identified, 115 patients (25%) and 252 patients (56%), respectively, experienced an iAE and postoperative complication. Major iAEs (grade ≥3) were observed in 15 patients (3%) and major postoperative complications (grade ≥3) were noted in 80 patients (18%). The most common iAE was vascular injury (112 of 132 events; 85%), which occurred in 92 patients (20%), and the most frequent postoperative complication was ileus, which occurred in 121 patients (27%). Original and postchemotherapy retroperitoneal mass size, nonretroperitoneal metastases, intermediate and/or poor International Germ Cell Cancer Collaborative Group classification, previous RPLND, elevated tumor markers at the time of RPLND, and anticipated adjuvant surgical procedures increased the risk of both iAEs and postoperative complications. Patients who experienced an iAE were significantly more likely to experience a postoperative complication (odds ratio, 2.50; 95% confidence interval, 1.58‐3.97 [ P < .001]). Conclusions: In what to the authors' knowledge is the first analysis of PC‐RPLND using validated classifications for both iAEs and postoperative complications, advanced disease and surgical complexity significantly increased the risks of major iAEs and postoperative complications. Standardized reporting of adverse perioperative events allows providers and patients to appreciate the consequences of PC‐RPLND during counseling and decision making. Abstract : Postchemotherapy retroperitoneal lymphadenectomy (PC‐RPLND) is an essential, yet potentially morbid, therapy for the management of patients with advanced germ cell tumors. In this large series of patients with testicular cancer, the authors use validated classifications of severity to demonstrate that advanced disease and surgical complexity significantly increase the risks of major intraoperative adverse events and postoperative complications in patients undergoing PC‐RPLND.